Dataset of sediment cores and box cores collected in Central Basin, Ross Sea (Antarctica) - Colizza, Ester; Torricella, Fiorenza; Capotondi, Lucilla (Zenodo, 2024)
dataset of sediment cores and box cores collected in Central Basin, Ross Sea (Antarctica)